Radio quiet and radio notification zones characteristics for radio astronomy in medium densely populated areas and humid tropical countries - Zamri Z. Abidin; Zulfazli Rosli; Mohd S. M. Radzi; Noraisyah M. Shah; Mahidzal Dahari; Farah Ramadhani; Mohd Ifwat Bin Mohd Ghazali; Bahman Azarbad; Ungku F. S. U. Ibrahim; Norsiah Hashim (Society of Photo-Optical Instrumentation Engineers, 2024)
Indexed by WOS/Scopus/ERA